Cross-cutting lessons from the Decision-Maker Led Implementation Research initiative - Arielle Mancuso; Shahira Ahmed Malm; Alyssa Sharkey; A. S. M. Shahabuddin; Zubin Cyrus Shroff (BMC, 2021)
Abstract Background Almost 20 million children under one year of age did not receive basic vaccines in 2019, and most of these children lived in low- and middle-income countries. Implementation research has been recognized as an emerging area that is critical to strengthen the implementation of interventions proven to be effective. As a component of strengthening implementation, WHO has called for greater embedding of research within decision-making processes. One strategy to facilitate the embedding of research is to engage decision-makers as Principal Investigators of the research. Since 2015, the Alliance for Health Policy and Systems Research within the WHO and the United Nations Children's Fund have supported decision-maker led research by partnering with Gavi, the Vaccine Alliance, in an initiative called "Decision-Maker Led Implementation Research". This synthesis paper describes the cross-cutting lessons from the initiative to further understand and develop future use of the decision-maker led strategy. Methods This study used qualitative methods of data collection, including a document review and in-depth interviews with decision-makers and researchers engaged in the initiative. Document extraction and thematic content analysis were applied. The individual project was the unit of analysis and the results were summarized across projects. Results Research teams from 11 of the 14 projects participated in this study, for an overall response rate of 78.6%. Most projects were carried out in countries in Africa and conducted at the sub-state or sub-district level. Seven enablers and five barriers to the process of conducting the studies or bringing about changes were identified. Key enablers were the relevance, acceptability, and integration of the research, while key barriers included unclear results, limited planning and support, and the limited role of a single study in informing changes to strengthen implementation. Conclusions Decision-maker led research is a promising strategy to facilitate the embedding of research into decision-making processes and contribute to greater use of research to strengthen implementation of proven-effective interventions, such as immunization. We identified several lessons for consideration in the future design and use of the decision-maker led strategy.